Cognitive function and nonfood-related impulsivity in post-bariatric surgery patients - Georgiadou, Ekaterini; Gruner-Labitzke, Kerstin; Köhler, Hinrich; de Zwaan, Martina; Müller, Astrid (Frontiers in Psychology, 2014)
Initial evidence that cognitive function improves after bariatric surgery exists. The post-surgery increase in cognitive control might correspond with a decrease of impulsive symptoms after surgery. The present study investigated cognitive function and nonfood-related impulsivity in patients with substantial weight loss due to bariatric surgery by using a comparative cross-sectional design. Fifty post-bariatric surgery patients (postBS group) who had significant percent weight loss (M = 75.94, SD = 18.09) after Roux-en-Y gastric bypass (body mass index, BMI Mpost = 30.54 kg/m2, SDpost = 5.14) were compared with 50 age and gender matched bariatric surgery candidates (preBS group) (BMI Mpre = 48.01 kg/m2, SDpre = 6.56). To measure cognitive function the following computer-assisted behavioral tasks were utilized: Iowa Gambling Task, Tower of Hanoi, Stroop Test, Trail Making Test-Part B, and Corsi Block Tapping Test. Impulsive symptoms and behaviors were assessed using impulsivity questionnaires and a structured interview for impulse control disorders. No group differences were found with regard to performance-based cognitive control, self-reported impulsive symptoms and impulse control disorders. The results indicate that the general tendency to react impulsively does not differ between pre-surgery and post-surgery patients. The question of whether nonfood-related impulsivity in morbidly obese patients changes post-surgery should be addressed in longitudinal studies given that impulsive symptoms should be considered potential targets for pre- as well post-surgery interventions.